Dynamics types of land use and land cover to determine time of the value erosion coefficient criticism in Keduang Watershed. Issue 1 (1st February 2022) - Ahmad,; Utomowati, R
Abstract: This research aims to: (1) Determine the trends in change of the type of plants planted by the community within a year for each type of land use in Keduang Watershed; (2) Understand the dynamics of land cover in each land-use unit in Keduang Watershed; (3) Determine the influential factors of the dynamics land use and land cover in Keduang Watershed; (4) Understand in what circumstances the criticality of erosion coefficient (C value) occurs in Keduang Watershed. The methods used are: (1) analysis of trends in changes of crop types are determined based on the rotation of the plant species planted by farmers in each land use unit; (2) The dynamics of land cover determined by the percentage (%) of the plant canopy area that covers each land use unit; (3) The affecting factor of the dynamics of land use and land cover are determined based on the causative factor of land-use change and land cover dynamics; (4) the time of occurrence of the critical value of the erosion coefficient is determined based on comparing the time of high rainfall and the lowest decrease of land cover. The result shows that: (1) In Keduang Watershed, crop rotation occurs in rainfed-rice fields and moorland; (2) Seasonal change is the main factor for change of land use and land cover; (3) The critical period of the erosion coefficient value in Keduang Watershed occurred in November.